Fish diversity in the Río de la Plata and adjacent waters: an overview of environmental influences on its spatial and temporal structure. Issue 1 (28th April 2016) - Jaureguizar, A. J.; Solari, A.; Cortés, F.; Milessi, A. C.; Militelli, M. I.; Camiolo, M. D.; Luz Clara, M.; García, M.
Abstract : The fish diversity and the main environmental factors affecting the spatial distribution of species, life history stages and community structure in the Río de la Plata (RdP) and adjacent waters are reviewed and analysed, with emphasis on the functional guild classification. The functional guild classification indicated that most species in the RdP were marine stragglers, zoobenthivores and oviparous species, although the biomass was dominated by estuarine species. Salinity had a stronger influence than temperature on the spatial pattern for all life stages, shallower and fresher waters are the preferred habitats of neonates and juveniles. During the breeding season (spring‐summer), adults showed an intrusion into the inner part of RdP or to its adjacent nearshore waters from the offshore waters for spawning or mating, respectively. Variations in river discharge and wind patterns greatly affected the spatial extent of estuarine water, which ultimately influenced the domain of the main life‐history stages (juveniles or adults) for both marine and estuarine fishes, as well as species and fish assemblage composition. The strong environmental gradient restricts some species and life‐history stages to a particular section and defines three main fish assemblage areas. The composition of the fish assemblage is indicative of the recruitment of freshwater and marine species to the estuary in opposite ways, determined by the vertical stratification. Seasonal changes in the species composition were related to migration as a result of salinity and temperature variations and reproductive migrations to spawning and mating areas. This overview reveals that the RdP is under environmental variations that are likely to produce modifications to fish distribution and abundance that affect its fisheries. This context plus fish stock declines and changes in exploitation patterns could amplify the magnitude of the variations in the fisheries resources availability and affect the sustainability of fishing communities.